Fetal intra-abdominal umbilical vein varix: a rare perinatal diagnosis - Mehboob, Rabia; Mumtaz, Hira; Ahmed, Mustafa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Fetal intra-abdominal umbilical vein varix (FIUVV) is a rare perinatal diagnosis. It can be missed easily on routine 2D ultrasound. It is focal dilatation of umbilical veins diagnosed prenatally on ultrasound. we are reporting here the case of FIUVV this case to raise awareness about the FIUVV as it can be missed easily on routine ultrasound scan. A 31-year-old lady presented in her third pregnancy. She has had two previous uncomplicated normal vaginal births at term. Her scan at 31 weeks of gestation demonstrated estimated fetal weight at 64th centile, normal liquor volume and normal Doppler studies. A three-vessel umbilical cord and a small intra-abdominal umbilical vein varix of 12×15 mm. Further scan that was performed at 37 weeks of gestation showed increased in size of FIUVV of about 18×14 mm, however, no turbulence flow noted at the site of varix. Estimated fetal weight calculated as 2876 grams with normal Doppler studies and liquor volume. She has been advised delivery around 37-38 weeks. She is induced at 38 weeks of gestation followed by normal vaginal birth of an alive baby with APGAR scores of 9 at 1 minute, 10 at 5 minutes and 10 at 10 minutes of life. Baby initial checks didn’t show any congenital abnormalities.